Simulasi Sistem Antrian Inbound Outbound Truk Kontainer untuk Meminimasi Waktu Pelayanan - Khotobi, Mochamad; Nuha, Hilyatun; Murnawan, Hery (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The increasing activity of container handling in depots requires improvements in service efficiency, particularly in inbound and outbound processes that often experience long truck queues. PT Seacon Bintang Sejahtera Surabaya faces delays that exceed its Key Performance Indicator (KPI) of 35 minutes. This study aims to analyze the performance of the queueing system and propose improvements to minimize service time using Arena simulation software. Primary data were obtained through direct observation, including truck arrival times, service start times, and service durations. The simulation model was validated to match real operational conditions, followed by testing several improvement scenarios such as additional servers and optimized service flow. The simulation results indicate that the proposed scenarios significantly reduce waiting times compared to the existing system, providing a basis for improving operational performance in container depot services